C. G. N. Mascie-Taylor (ed.): The Anthropology of Disease - Aagaard-Hansen, Jens (Tidsskriftet Antropologi, 2019)
C. G. N. Mascie-Taylor (ed.): The Anthropology of Disease Anmeldes af Jens Aagaard-Hansen